Language And Humour In Charles Dickens’s Little Dorrit - Diesel, Sophia Celina (Em Tese, 2018)
The language of Charles Dickens evolved throughout his career, characteristically becoming more sophisticated in his later novels such as Little Dorrit. Considered by the critic and the public more serious and calculatedly darker than previous successes those novels are as well full of humour and irony. The difference is that the humour also became more sophisticated and poignant. This essay discusses – supported by criticism such as The Dark Effigy: a study of Dickens’s Imagination by professor John Carrey from Oxford University – the violence implied by the author in the humour of his mature language and how this humour is produced along with misunderstandings and blocked dialogue of characters in Little Dorrit. The problematic communication produces an atrophied flow of energy which matches the prison theme of the novel enabling those characters to be free and happy, and emphasising the causes for this problems in their also atrophied Victorian society.